Maintainability and evolvability of control software in machine and plant manufacturing — An industrial survey. (November 2018) - Vogel-Heuser, Birgit; Ocker, Felix
Abstract: Automated Production Systems (aPS) have lifetimes of up to 30–50 years, throughout which the desired products change ever more frequently. This requires flexible, reusable control software that can be easily maintained and evolved. To evaluate selected criteria that are especially relevant for maturity in software maintainability and evolvability of aPS, the approach SWMAT4aPS+ builds on a questionnaire with 52 questions. The three main research questions cover updates of software modules and success factors for both cross-disciplinary development as well as reusable models. This paper presents the evaluation results of 68 companies from machine and plant manufacturing (MPM). Companies providing automation devices and/or engineering tools will be able to identify challenges their customers in MPM face. Validity is ensured through feedback of the participating companies and an analysis of the statistical unambiguousness of the results. From a software or systems engineering point of view, almost all criteria are fulfilled below expectations. Graphical abstract: Highlights: Uncovering weaknesses of software engineering for PLC based control software in machine and plant manufacturing. Identification of stepping stones for such companies to update software in the machines'/plants' operation phase. Appropriate variant and version management being a prerequisite for software updates in operating machines and plants. Gap in between computer science and aPS regarding model based software engineering and more sophisticated approaches like object orientation for control software. SWMAT4aPS+ evaluates requirements based on self-assessed questionnaire.